Transformasi Digital: Dampak E-Commerce terhadap Perkembangan E-Business di Indonesia - Putri, Revita Pratama; Fasa, Muhammad Iqbal (Journal of Social Science and Multidisciplinary Analysis, 2025)
Digital transformation is now one of the main factors in changing the business ecosystem in Indonesia, especially with the rapid development of e-commerce. E-commerce acts as a multiplier in driving e-business growth, expanding market reach, improving operational efficiency, and changing people's consumption patterns. This study aims to analyze the impact of ecommerce on the development of e-business in Indonesia by exploring important factors, such as technology adoption by MSMEs, changes in consumer behavior, and challenges faced in the current digital era. The results show that while e-commerce offers great opportunities for businesses, there are still challenges to be faced, such as intense competition, cybersecurity, and the digital divide. Therefore, close collaboration between the government, industry players, and society is needed to create an inclusive and sustainable e-business ecosystem.